Nilai Moral Tari “Belagak Jadi Balak” Adaptasi Dari Legenda Putri Pinang Masak Kabupaten Ogan Ilir - Azzahra, Azzahra (PPSDP Undergraduate Journal of Educational Sciences, 2025)
The dance performance, which tells the story of Putri Pinang Masak, serves as a medium to convey important moral values, especially regarding education, gender equality and cultural heritage preservation. Through its strong characters, the performance successfully educates the audience on the importance of sharing knowledge and skills, and demonstrates that the fight for gender equality is a collaborative effort that involves all levels of society. In addition, the story emphasizes the important role of cultural heritage in maintaining community identity and pride, especially in the midst of globalization. By integrating elements of local culture, the performance is not only entertaining, but also encourages the audience to reflect on and internalize the moral values contained in the story, thus contributing to efforts to create a more inclusive and equitable society.